ENVIRONMENTAL AND SPATIAL ASPECTS OF POLLUTION OF THE TERRITORY OF TERNOPIL REGION WITH MICROPLASTIC MASSES (Regional aspects of productive forces development of Ukraine, 2024)
Introduction. The article addresses the critical issue of environmental pollution caused by the plastic waste. This problem has drawn the attention of researchers due to the vast physical volumes ofplastic waste, their unique behavior in the environment, and their adverse impact on human health. The disposal of plastic waste has become a matter of great concern, and the destructive effects of externalenvironmental factors cause the breakdown of polymers into microparticles, leading to microplastic pollution. This form of pollution is a significant environmental issue due to its uncertain nature, and asubstantial portion of plastic waste remains in the environment, becoming invisible. This lack of microplastic pollution visual comprehension often diverts attention from this issue. Currently, the problem of pollution by microplastic masses is mainly considered globally. Therefore, it is crucial to shift our attention toward the dangers of microplastic contamination at the local and mesoregional levels. In this paper, the environmental and spatial aspects of microplastic pollution in the Ternopil region wereexamined, focusing on the peculiarities of their formation and distribution in the area.The purpose of the article is to study the spatial aspects of the formation, distribution and accumulation of microplastic masses at the regional level.Research methods. The methods of analysis and synthesis, systematic generalization, creation of geographical maps were used in the preparation of the scientific publication.The results. Identified and analyzed various sources of microplastic pollution in the Ternopil region, including point, areal, dispersed, and linear sources, and the processes of formation and migration of microplastics within the region along with sectoral features of environmental pollution in the region caused by microplastics. Revealed peculiarities of the formation of this type of pollution as aconsequence of the high level of agricultural development of the region, development of the logistics, influence of urbanization processes, and the development of the management and waste managementsystem. Considered the role of microplastics in transportation at the regional and interregional levels of environmentally hazardous chemicals and their accumulation in ecosystems. In the Ternopil region, soilpollution with subsequent degradation of microbiomes of soil ecosystems, as well as destruction of water ecosystems, is particularly significant. All this is a direct result of the rapid development of agriculturaltechnologies for growing agricultural crops. A significant role in spatial assessments of territory pollution is played by the transport factor, primarily the development of road transport.